Remote Irrigation Control Based on LoRa Technology and Fuzzy PID Algorithm - Yuliang Li (IEEE Access)
Due to the dual challenges of limited communication distance and insufficient adaptability to complex environments in remote irrigation control technology, this study combines Long Range Radio (LoRa) technology and Proportional-Integral-Derivative (PID) algorithm to construct a remote irrigation control system and improve the intelligence of irrigation modes. The perception layer architecture of the system and its terminal devices collect soil moisture and other parameters, which are then transmitted to the upper computer through the LoRa module. The fuzzy PID algorithm and its controller use soil moisture parameters to adjust irrigation parameters, enabling the LoRa network to effectively convey irrigation instructions and improve water resource utilization. After systematic simulation analysis and actual testing, when the communication distance was 700m, the packet loss rate of the collection node in complex terrain was 0.95%, and the packet loss rate of the receiving node was 1.06%. Compared with the packet loss rate in open terrain, the average value was increased by about 2.5%. In irrigation mode, the irrigation time of the orchard had an error of less than 0.7% compared to the system calculation, and the minimum irrigation time was 10.06 seconds. Therefore, the remote irrigation control system based on LoRa technology and fuzzy PID algorithm has stability and superiority, achieving high efficiency and precision applications, which is conducive to promoting the digitization and sustainable development of agricultural production activities.